Biodiversity of the aculeate wasps (Hymenoptera: Aculeata) of the Arabian Peninsula: Vespoidea, Sapygidae - Gadallah, Neveen S.; Brothers, Denis J. (Zootaxa, 2020)
An updated checklist of the Arabian species of Sapygidae is provided here. The list includes a single identified valid species in the subfamily Sapyginae: Asmisapyga guichardi Gusenleitner. Distributions, both on the Peninsula and extra-limital, are provided; the species is not endemic to the Arabian Peninsula.